PENGGUNAAN METODE ASPECT SENSITIVITY DALAM PENENTUAN TINGGI LAPISAN TROPOPAUSE DI SAAT MJO AKTIF MELINTAS KAWASAN KOTOTABANG DAN SEKITARNYA - Eddy Hermawan; Irma Nurlela; Tri Wahyu Hadi (Lembaga Penerbangan dan Antariksa Nasional, 2007)
This paper is mainly concerned to the utilization of aspect sensitivity (Pv/Po) method to define the tropopause height variation over the equatorial Indonesia, nearby Kototabang (0,2˚S; 100,32˚E), Bukittinggi, West Sumatera using the Equatorial Atmosphere Radar (EAR), especially during the Coupling Processes Equatorial Atmosphere (CPEA) Campign I in 2004 is already done. It is very important to be done since the tropopause is the buffer layer between troposphere and stratosphere (and also contrary) that usually called as the Stratosphere-Troposphere Exchanged (STE) (Holton, 1996). Validation's results with the radiosonde data shows that (Pv/Po relatively higher that radiosonde data. They are about 712 meter and 961 meter for Cold Point Tropopause (CPT) and Lapse Rate Tropopause (LRT) version, respectively. The mean difference between CPT and LRT itself is about 248 meter. This is enough valid considering to the maximum difference between of them not more 500 meter ( Haynes and Shepherd, 2001). This result then be applied in determining of tropopause height variation over Kototabang especially when the Madden-Julian Oscillation (MJO) passed over this region from November to December 2001. It shown that there are no significant differences between MJO active and no active on the tropopause height determination about 17.98 km and 17.73 km, respectively. The most interest is the tropopause height variation is larger during the MJO active than non active.To get the better understanding of tropopause height variation, especially with good time and spatial height resolution, the utilization of ERA and other instruments Kototabang are very needed.